Turbulence Power Spectra in Regions Surrounding Jupiter's South Polar Cyclones From Juno/JIRAM. Issue 7 (13th July 2020) - Moriconi, M. L.; Migliorini, A.; Altieri, F.; Adriani, A.; Mura, A.; Orton, G.; Lunine, J. I.; Grassi, D.; Atreya, S. K.; Ingersoll, A. P.; Dinelli, B. M.; Bolton, S. J.; et al.
Abstract: We present a power spectral analysis of two narrow annular regions near Jupiter's South Pole derived from data acquired by the Jovian Infrared Auroral Mapper instrument onboard NASA's Juno mission. In particular, our analysis focuses on the data set acquired by the Jovian Infrared Auroral Mapper M‐band imager (hereafter IMG‐M) that probes Jupiter's thermal emission in a spectral window centered at 4.8 μm. We analyze the power spectral densities of circular paths outside and inside of cyclones on images acquired during six Juno perijoves. The typical spatial resolution is around 55 km pixel −1 . We limited our analysis to six acquisitions of the South Pole from February 2017 to May 2018. The power spectral densities both outside and inside the circumpolar ring seem to follow two different power laws. The wave numbers follow average power laws of −0.9 ± 0.2 (inside) and −1.2 ± 0.2 (outside) and of −3.2 ± 0.3 (inside) and −3.4 ± 0.2 (outside), respectively, beneath and above the transition in slope located at ~2 × 10 −3  km −1 wave number. This kind of spectral behavior is typical of two‐dimensional turbulence. We interpret the 500 km length scale, corresponding to the transition in slope, as the Rossby deformation radius. It is compatible with the dimensions of a subset of eddy features visible in the regions analyzed, suggesting that a baroclinic instability may exist. If so, it means that the quasi‐geostrophic approximation is valid in this context. Plain Language Summary: Juno has revealed extraordinary and unexpected dynamics in Jupiter's polar regions. The clouds imaged in the infrared and visible parts of the spectrum by JIRAM and JunoCam, respectively, are organized around a central cyclone in regular patterns of eight (North Pole) and five (South Pole) cyclones. We studied the spatial and temporal variability of the regions immediately outside the cyclonic circulations at the South Pole. By analyzing multiple JIRAM images at five microns, geographically merged and appropriately filtered and sampled, we found that cloud patterns poleward and equatorward the ring of cyclones at Jupiter's South Pole, may originate from flow instabilities not linked to vortices' dynamics. These instabilities can have their origin in the horizontal pressure and temperature gradients rather than in the cyclonic circulations and their interactions, also considering the low speed values of the wind field in those regions. Key Points: Dynamics consistent with quasi‐geostrophic 2‐D turbulence in the Jupiter South Polar regions surrounding the main cyclonic circulations The forcing scales resulting from these analyses indicate that baroclinic instabilities may exist in the analyzed regions Many waves have been revealed in the Jupiter South Polar region by JIRAM images